“The Standard of Revolt”: Revolution and National Independence in Moore’s Lalla Rookh - Vail, Jeffery (Romanticism on the Net)

(untitled) (Université de Montréal, 2005)
This article argues that Thomas Moore's collection of narrative poems Lalla Rookh, an Oriental Romance (1817), by presenting disguised versions of the French Revolution and the Irish Rebellion of 1798, condemns the former but justifies the latter. As the “National Poet” and preeminent literary voice of Ireland, as well as a witness of the 1798 Rebellion, Moore was particularly concerned with the subjects of national independence and armed revolution.  The Veiled Prophet of Khorassan depicts a monstrous embodiment of French Jacobinism in the form of the eighth-century false prophet Mokanna, who hides his horrific face behind a beautiful veil.  In contrast to Mokanna's corrupt and evil revolution, the national uprising depicted in The Fire-worshippers is depicted as noble and justified.  Moore intended this story of Persian resistance to Arab Muslim colonizers as an allegory of Irish Catholic resistance to England, with special reference to the 1798 Rebellion. The prose linking narrative of Lalla Rookh also contains a political dimension, looking forward to possible political reforms that would make armed struggle unnecessary.